PENGEMBANGAN BAHAN AJAR MATERI INDUKSI MATEMATIKA DAN TEORI BINOMIAL BERBASIS PEMBUKTIAN - Nurafni Nurafni; Asih Miatun; Hikmatul Khusna; Hella Jusra (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
Students' ability in solving argumentation in mathematical induction and binomial theory is still lacking based on the results of the exam, so that evidence-based teaching materials are prepared. This study uses design research methods with the subject from 2nd semester students of the Mathematics Education Study Program. This research is a development research consisting of 6 stages: Identification of needs, Planning, Initial product development, Initial product testing, Product revision, Field trials so as to produce teaching materials. The results of the lecturer and student validation show that the teaching materials are valid and feasible to use with an average score of 45 and 45,9333. While the test of the effectiveness of teaching materials used using the t-test obtained results that ttest> ttable, 5.83 > 2.11 which means there is an increase in the average value of students before and after using teaching materials. With the increase in value, it indicates that the instructional materials prepared are effectively used.